Hydrogen sulfide‐mediated resistance against water avoidance stress‐induced gastritis by maintenance of gastric microbial homeostasis. Issue 1 (22nd October 2019) - Han, Yingnan; Li, Ya; Hu, Zhekai; Wang, Xiao; Liu, Junze; Ren, Xue; Yu, Yanbo; Li, Yan; Li, Wenjuan; Sun, Yundong
Abstract: Chronic persistent stress is an important cause of gastritis, but the underlying mechanism remains to be further researched, especially the role of the gastric microbiota in this process. Here, we used the water avoidance stress (WAS) test in mouse models for chronic stress‐induced gastritis to investigate the underlying mechanisms of this disease. The effect of stress on the gastric microbiota was analyzed based on 16S rRNA sequencing; the changes in hydrogen sulfide (H2 S) and inflammatory cytokine levels in gastric tissues were detected by Western blotting, ELISA, immunofluorescence, and qRT‐PCR. Hematoxylin and eosin staining was used as an indicator of the gastritis histological score. This finding is consistent with previous studies showing that gastric H2 S is negatively associated with the inflammatory index and might protect the gastrointestinal tract from inflammation. WAS‐induced gastritis was associated with a reduction in H2 S release, which appeared to affect the homeostasis of the gastric microbiota of mice. Inflammation and microbial dysbiosis were partially reversed by sodium hydrosulfide (NaHS) and vitamin B6 (VB6) supplementation, suggesting the therapeutic potential of VB6 supplementation for the treatment of stress‐induced gastritis. Gastritis has a serious impact on health and quality of life. An increasing number of people are suffering from chronic gastritis linked to a high‐stress lifestyle, and our research provides clues for the prevention and treatment of stress‐induced gastritis. Abstract : Chronic persistent stress is an important cause of gastritis, but the underlying mechanism remains to be further researched. Here, we used the water avoidance stress test in mouse models for chronic stress‐induced gastritis to investigate the underlying mechanisms of this disease. Stress‐induced gastritis was associated with a reduction in hydrogen sulfide release, which appeared to affect the homeostasis of the gastric microbiota of mice.